Assessment of P300 ERP Component, Cortical Scalp Mapping and Correlation With Age in Children With Dyslexia Using True and Pseudo Words in the Malay Language: A Quantitative Cross sectional Study in Kelantan, Malaysia - Siti Atiyah, Ali; Tahamina, Begum; Faruque, Reza; Nor Asyikin, Fadzil; Faiz, Mustafar (Fakulti Perubatan dan Sains Kesihatan, UPM PRESS, 2020)
Introduction: Children with dyslexia have disparate visual attention while reading varied structures of grapheme-phoneme that have different congruency. Exploring more related with attention and reading disability, we investigated the visual attention, topographic mapping and correlation of ages of children with dyslexia using ERP study. Methods: A quantitative cross-sectional, non-interventional study was performed with simple randomization to select participants. A total of 24 children were recruited into two groups; control (n=12) and dyslexic (n=12) groups. 128-ERP net was used for ERP experiment. Congruent (true meaningful Malay, 80%) and incongruent (meaningless, 20%) words were used for stimuli. Participants pressed button ‘1' and ‘2' when they saw congruent and incongruent words, respectively. Amplitudes and latencies of P300 ERP component were analysed at 19 electrode sites in 10-20 system. Results: Dyslexics evoked significantly higher P300 amplitude at T6 and shorter P300 latency at Fp1 areas compared with the control group. Moreover, pseudo word stimulations showed a high P300 voltage distribution in the prefrontal and right occipital area in the dyslexics, whereas there was more activation in the bilateral occipito-parietal areas in the controls. Significantly moderate positive correlation was found in the control group at F3, F7 and negative correlation in the dyslexic group at T4 areas for P300 latency. Conclusion: Children with dyslexia have higher visual attention with fronto-central topographic distribution for true Malay words and prefrontal and right occipital areas for pseudo Malay words. Age correlation results indicated that attention is directly related to the brain maturity of children.